A review on the toxicity of insecticides against brown planthopper (Nilaparvata lugens) in paddy / Mohd Hasmirul Hasran - Hasran, Mohd Hasmirul (Faculty of Plantation and Agrotechnology, 2017)
The brown planthopper (BPH), Nilaparvata lugens is the main pest of paddy in Asian region. The usage of chemical insecticides is widely and heavily by the farmers in order to control BPH. Therefore, to ensure this will not happen, farmers used chemical to control the outbreaks of brown plant hopper. High rates of insecticide application could kill natural enemies which known as beneficial insect in paddy fields. There are examples of the common insecticides use to control BPH which are Carbofuron, Imidacloprid and Chlorpyrifos. Some studies proved that Carbofuron and imidacloprid are the most effective insecticides to control BPH population as compared to chlorpyrifos. Carbofuron is the effective insecticides and imidacloprid less effective in controlling the BPH. Carbofuron is highly toxic and imidacloprid is moderate toxic to BPH. Chlorpyrifos is the less toxic to the BPH. The resistance towards all these insecticides still low. In some countries in Asia have no reported issues about the resistance of BPH towards all these insecticides but for some countries have reported that the level of resistance is still low. Thus, the effective insecticides among theseinsecticides is Carbofuron because not only reducing massive amount of BPH population and also increase the yield for paddy.